The spectacular fossils of the 'water margin': the Cambrian biota of Chengjiang, Yunnan, China. (November 2016) - Williams, Mark; Siveter, David J.; Siveter, Derek J.; Gabbott, Sarah E.; Ma, Xiaoya; Purnell, Mark A.; Cong, Peiyun
Abstract : Shi Nai'an's fourteenth century Chinese epic 'Water Margin' tells of the release of 36 heavenly spirits and 72 baleful stars from their captivity beneath a tablet of stone at Mount Longhu in Jiangxi Province. They are reincarnated as the 108 heroes of the Liangshan marsh in Shandong Province, who rise against an unjust world. The virtuous exploits of the '108' were brought to life through the cathode‐ray screens of 1970s television sets, as the TV series The Water Margin introduced heroes like Lin Chong battling his evil nemesis Gao Qiu. Far to the west of Jiangxi Province and several hundred years after the Water Margin during the summer of 1984, a young scientist from Nanjing was working amongst the hills and lakes of southern Yunnan Province. He too overturned a stone slab, releasing from their half‐billion year captivity a cornucopia of new Chinese legends. His name was Xianguang Hou and he had made one of the most momentous fossil discoveries in history, uncovering the exceptionally preserved marine fossils of the Chengjiang biota from the ancient water margin of Cambrian seas.